Pendampingan Pembuatan Krim Bawang Dayak Khas Kalteng sebagai Anti Acne di SMK Farmasi Muhammadiyah Palangka Raya - Syahrida Dian Ardhany; Susi Novaryatiin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Bawang dayak is a typical plant of Central Kalimantan in a study can be used as an antiacne agent, but unfortunately the knowledge and utilization of this medicinal plant is still minimal, in addition, the lack of interest of young generation in learning the knowledge of traditional medicine and development of natural materials can make this traditional heritage gradually become extinct. The method of increasing the knowledge provided was giving material and video demonstration on the making of anti-acne cream of bawang dayak which was analyzed from the results of the pretest and posttest. From the results, it can be concluded that there is an increase in knowledge of students about bawang dayak as antiacne (P=0.002 < 0.05).